Pelatihan Basic Life Support (BLS) Pada Siswa Madrasah Aliyah Swasta (MAS) Kaidipang Boroko Timur Kecamatan Kaidipang Kabupaten Bolaang Mongondow Utara - Faradilla Miftah Suranata; Riska Riska; Intan Safina; Safita Gay; Rosida Tidore; Delia Umalekhoa; Monalisa Mokodompit (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Number one killer in the world is a sudden cardiac arrest. It's one of those depressive conditions that can happen anywhere, anytime, and to anyone. The number of deaths from cardiovascular disease in Indonesia is 14.4%. One of the measures that can prevent deaths is by performing Basic Life Support (BLS) which is the initial treatment of a person who has a cardiac arrest and breathing arrest. So it is necessary to provide basic life support (BLS) training to civilians to prevent deaths. The purpose of this community dedication is to improve the knowledge and skills of students of MAS Kaidipang district of North Bolaang Mongondow. The activities of public dedication are conducted in the form of training by providing material and demonstration of basic life support (BLS) steps. The results of this training are achieved improvement of knowledge and skill in students of MAS Kaidipang.